Excision of giant fibroadenoma of the right breast managed with skin-sparing mastectomy and immediate expander reconstruction: a case report - R. Babu, Akshay S.; Suresh, Priyanka; Chandrabhan Singh, Ramesh Babu (International Surgery Journal, 2026)
Giant fibroadenomas are uncommon benign breast tumours, typically defined as lesions larger than 5 cm or 500 g or occupying most of the breast volume. They may cause marked breast asymmetry, skin distortion, and psychosocial distress, and often mimic phyllodes tumours on clinical and radiological assessment. We report the case of a 33-year-old woman presenting with a progressively enlarging right breast mass. Imaging revealed a well-circumscribed, heterogeneous lesion measuring 21×17×17 cm (estimated maximal diameter 30 cm) consistent with a giant fibroadenoma. The patient underwent complete excision via a partial skin-sparing right mastectomy, including nipple–areola complex removal, followed by immediate expander implant reconstruction. The excised specimen weighed 5.3 kg, representing one of the largest fibroadenomas reported in the literature. Histopathological analysis confirmed a complex fibroadenoma without atypia or malignancy. Postoperative recovery was uneventful, with excellent cosmetic and functional outcomes and no evidence of recurrence on follow-up. This case highlights an extreme presentation of giant fibroadenoma successfully managed with complete excision and immediate oncoplastic reconstruction. Early recognition, detailed imaging evaluation, and multidisciplinary surgical planning are essential to distinguish giant fibroadenoma from phyllodes tumour and to achieve optimal oncological safety with satisfactory aesthetic results.